Design, synthesis, in vitro and in silico characterization of plastoquinone analogs containing piperidine moiety as antimicrobial agents - Yildiz, Mahmut; Yildirim, Hatice; Bayrak, Nilufer; Cakmak, Selin Melis; Mataraci-Kara, Emel; Ozbek-Celik, Berna; Otsuka, Masami (Elsevier, 2023)
The design and development of novel antibacterial and/or antifungal lead structures are urgently required to cope with the increasing antimicrobial resistance. Inspired by the literature and our previous studies, we designed and synthesized new Plastoquinone analogs (PQ1-12) containing piperidine moiety via one-pot reaction of commercially available 2,3-dimethylhydroquinone (1) with piperidine analogs by varying a heteroatom within the piperidine moiety or an alkyl group and (hetero)cyclic structure attached to the piperidine moiety. The chemical structures of the PQ analogs were determined by spectroscopic methods (FTIR, NMR, Mass, and X-ray). The antimicrobial activity of the PQ analogs was investigated against both bacterial and fungal strains. The tested PQ analogs showed significant antibacterial activity and weak to moderate antifungal activity. PQ2 and PQ7 exhibited favorably strong interactions with fungal CYP51 and S. aureus DNA gyrase, respectively, in silico. Both compounds displayed favorable physicochemical and pharmacokinetic properties.(c) 2022 Elsevier B.V. All rights reserved.
Keywords: Antibacterial activity; Antifungal activity; Bactericidal effect; Plastoquinone; Quinone